THE INFLUENCE OF ONLINE REVIEW ON ONLINE HOTEL BOOKING INTENTION IN MANADO - Togas, Pricella T.; Kindangen, Paulus; Tumbuan, Willem J.F.A. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Increment of the number of hotels, creates a competitive value among each hotels. Because of that the customer needs additional information about the hotels to find the right hotel that they want to reserve. In online travel agent (OTA), there is a feature named online review. So online review could be a media for other customers in order to search information about an hotel but because of everyone could give their opinion freely it may also risky because of the reliable level of review that appears in online review. So this research aims to analyze the influence of online review on online hotel booking intention in Manado. This study uses quantitative method with causal analysis. Finding of this research shows that Usefulness and Comprehensiveness of online review influences online hotel booking intention in Manado significantly and Timeliness, Volume and Valence of online review does not have significant influence to the online hotel booking intention in Manado. The recommendation of this study that can be given for further research are recommended to conduct research on the business of online travel agent of airlines company.Â Keywords: online review, usefulness, timeliness, volume, valence, comprehensivenss, online booking intention, hotel